KOMUNIKASI PEMERINTAH DESA DALAM PERENCANAAN PEMBANGUNAN DESA SUATU STUDI DI DESA SOATOBARU KECAMATAN GALELA BARAT KABUPATEN HALMAHERA UTARA - DILAGO, WELDI; LALOMA, ALDEN; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2019)
The communication of the Soatobaru village government in the implementation of development wasimportant among all parties involved in the village development effort, especially between the villagegovernment and the community. Dissemination of development information that has been carried out untilnow is carried out through communication media from communicators to communicants, both thosehandled by the village government and the media. In the concept of communication, a communicator hereplays a very important role, why? Because a Communicator must have good communication skills so that acommunicant can capture messages quickly and accurately. In implementing village development forvillage-scale local authority, the village government needs to carry out development stages which include;Planning, Budgeting, Implementation, Reporting, Monitoring and Monitoring. Reliable indicators areknowledgeable communicators. The purpose of village development, as stated in Law No. 6 of 2014concerning Villages, is to improve human welfare and reduce poverty through the provision of basic needs,development of village facilities and infrastructure, development of local economic potential and sustainableuse of natural and environmental resources.Keywords: Communication, Village Government, Planning, Development